Cytological and proteomic evidence reveals the involvement of mitochondria in hypoxia-induced quality degradation in postharvest citrus fruit. (1st May 2022) - Li, Xin; Tian, Zhen; Chai, Yingfang; Yang, Hongbin; Zhang, Mingfei; Yang, Ce; Xu, Rangwei; Zhu, Feng; Zeng, Yunliu; Deng, Xiuxin; Wang, Pengwei; Cheng, Yunjiang
Highlights: The hypoxia-induced alterations in mitochondrial morphology and ultrastructure were characterized. The mitochondrial proteomes of wax-treated and the control were compared. Key hypoxia-responsive proteins were identified from mitochondrial proteome via WGCNA. Abstract: Hypoxia frequently occurs in postharvest logistics, which greatly influences fruit storability. Here, we for the first time studied the dynamic variations of mitochondrial morphology in living citrus fruit cells, and revealed that waxing treatment-induced hypoxia strongly triggered mitochondrial fission and fragmentation. Correspondingly, hypoxia caused a decline in mitochondrial membrane potential and mobility. Besides, impairment of energetic and redox status was also found in waxed fruit. The proteomic changes of mitochondria after waxing treatment were also characterized. Using weighted gene co-expression network analysis (WGCNA), we identified 167 key hypoxia-responsive proteins, which were mainly involved in fatty acid, amino acid and organic acid metabolism. Metabolite analysis verified that waxing treatment promoted the accumulation of several hypoxic metabolites, such as ethanol, acetaldehyde, succinic acid and γ-aminobutyric acid (GABA). Taken together, our findings provide new insights into the cytological and proteomic responses of mitochondria to hypoxia during fruit storage.